Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s00429-015-1084-x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct hippocampal functional networks revealed by tractography-based parcellation

Abstract: Recent research suggests the anterior and posterior hippocampus form part of two distinct functional neural networks. Here we investigate the structural underpinnings of this functional connectivity difference using diffusion-weighted imaging-based parcellation. Using this technique, we substantiated that the hippocampus can be parcellated into distinct anterior and posterior segments. These structurally defined segments did indeed show different patterns of resting state functional connectivity, in that the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
79
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 79 publications
15
79
3
Order By: Relevance
“…These studies have suggested that anterior aspects of the hippocampus send and receive input from areas including the dorsal and medial prefrontal cortices, and the amygdala and lateral temporal cortex, while the posterior aspects of the hippocampus have projections mainly to the mammillary bodies, anterior thalamus, and retrosplenial cortex, and receive input from the posterior cingulate and the occipital and temporal cortices . More recent reports have confirmed anterior and posterior hippocampal structural patterns in humans with tractography‐based parcellation and resting‐state connectivity . These divisions in pathways to the hippocampus provide a neuroanatomical basis for distinct functional cortical communication patterns.…”
Section: Section Three: Hippocampal Functional Organizationmentioning
confidence: 76%
“…These studies have suggested that anterior aspects of the hippocampus send and receive input from areas including the dorsal and medial prefrontal cortices, and the amygdala and lateral temporal cortex, while the posterior aspects of the hippocampus have projections mainly to the mammillary bodies, anterior thalamus, and retrosplenial cortex, and receive input from the posterior cingulate and the occipital and temporal cortices . More recent reports have confirmed anterior and posterior hippocampal structural patterns in humans with tractography‐based parcellation and resting‐state connectivity . These divisions in pathways to the hippocampus provide a neuroanatomical basis for distinct functional cortical communication patterns.…”
Section: Section Three: Hippocampal Functional Organizationmentioning
confidence: 76%
“…Unlike in typical Alzheimer’s disease where atrophy of the hippocampus does not show an anterior and posterior gradient, atrophy in definite PART showed an anterior predominance. This is important as there is evidence that the anterior and posterior hippocampus have different network connections [1], with the posterior hippocampus involved with retrieval and encoding aspects of episodic memory [18, 24, 58]. The lack of involvement of the posterior hippocampus in definite PART, therefore, likely explains why we did not observe any association between tau and the Auditory Verbal Learning Test Delayed Recall or the WMS-R Logical Memory Delayed Recall Test.…”
Section: Discussionmentioning
confidence: 87%
“…This heterogeneity is found both along the anterior-posterior axis of the hippocampus and across its different cytoarchitectonic subfields, which include the cornu ammonis fields (CA1-CA4 2 ), the dentate gyrus (DG), and the subiculum. The idea of distinguishing hippocampal substructures from neuroimaging data is not new; a few authors have measured the volume of hippocampal regions along the anterior-posterior axis, namely the head, body and tail (see Poppenk et al, 2013 for a discussion on strategies for long-axis segmentation), and have explored differential effects of aging or disease across these substructures (Driscoll et al, 2003;Gordon et al, 2013;Jack et al, 1997;Malykhin et al, 2008;La Joie et al, 2013), or assessed anteriorposterior gradient in normal hippocampal function and connectivity (Aggleton, 2012;Poppenk et al, 2013;La Joie et al, 2014a;Chase et al, 2015;Adnan et al, 2015). However, it is only more recently, with the development of more sophisticated neuroimaging methods and the emergence of high field MR scanners providing high (i.e.…”
Section: Introductionmentioning
confidence: 99%